The influence of pharmaceutical care in patients with advanced non-small-cell lung cancer receiving combination cytotoxic chemotherapy and PD-1/PD-L1 inhibitors - Wen Kou; Yan Yan Lin; Fei Su; Yue Xiang; Hui Qiao; Xin'An Wu; Xiao-Ming Hou (Frontiers Media S.A., 2022)
Background: Immune checkpoint inhibitors combined chemotherapy (ICIC) are widely used for various types of lung cancer in the past decade. However, ICIC related adverse events (AEs) are more serious than immune-related adverse events (irAE) or cytotoxic chemotherapy alone.Objective: This prospective interventional study aimed to evaluate the impact of the pharmaceutical care program in reducing adverse events and analyze pharmacy interventions in patients with NSCLC who receive ICIC therapies.Method: NSCLC patients were enrolled in this study, the pharmaceutical care program was introduced after patients received the second cycle ICIC therapies, and were followed by the pharmacist for 6 months after hospital discharge. The percentages of adverse events between patients in and after the first two cycles were analyzed and compared.Results: After the first two treatment cycles, the clinical pharmacist proposed 67 interventions in 30 patients. The most frequent types of intervention were drug discontinuation (40.3%, 27/67) followed by drug modification (14.9%, 10/67). There were significant decreases in AEs after the second cycle with respect to nausea (≥grade-2, 14% vs. 28.3%, p = 0.039), constipation (≥grade-2, 8.8% vs. 21.7%, p = 0.039), diarrhea (≥grade-2, 6% vs. 16.7%, p = 0.031), and myelosuppression (≥grade-2, 15.8% vs. 30.0%, p = 0.022).Conclusion: Provision of pharmaceutical care for NSCLC patients receiving ICIC therapies can optimize drug therapy and reduce adverse events.